Future Time Perspective and Career Decision Making Self-Efficacy: The moderator effect of Social Support and the mediator effect of Positive Affect - Febriyati, Zuli; Purwanto, Edy; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2023)
Many students lack skills to complete career developmental tasks due to low career decision making self-efficacy. Thus, the present study tried to examine the effects of future time perspective on career decision making self-efficacy through positive affect viewed from social support. It used an ex post facto correlational design with the samples of 366 senior high school students in Banyuasin Regency. Some instruments were used to collect the data, such as Career Decision Making Self-Efficacy (CDMSE), Future Time Perspective (FTP), Positive Affect and Negative Affect (PANAS), and Multidimensional Scale of Perceived Social Support (MSPSS) that have been validated in terms of validity and reliability. Findings indicated that future time perspective had a significant effect on positive affect increase and career decision making self-efficacy. Besides, there was another significant relation between positive affect and career decision making self-efficacy. Lastly, there found an indirect effect of future time perspective on career decision making self-efficacy through positive affect and a moderator effect of social support on the relationship between future time perspective and career decision making self-efficacy. These findings have confirmed the potential of future time perspective, positive affect and social support on career decision making self-efficacy.